2002
DOI: 10.1038/nmat800
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ferroelastic domains in ferroelectric thin films

Abstract: Dynamics of domain interfaces in a broad range of functional thin-film materials is an area of great current interest. In ferroelectric thin films, a significantly enhanced piezoelectric response should be observed if non-180 degrees domain walls were to switch under electric field excitation. However, in continuous thin films they are clamped by the substrate, and therefore their contribution to the piezoelectric response is limited. In this paper we show that when the ferroelectric layer is patterned into di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
372
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 532 publications
(394 citation statements)
references
References 17 publications
20
372
2
Order By: Relevance
“…Despite this level of consensus, recent experimental work hints that parasitic dielectric dead-layers might not be intrinsic at all, or if they are, their presence is much less obvious than originally thought: Initially in response to concerns that permittivity suppression might result from microstructural imperfections [34][35][36] or from substrate clamping [37], Saad et al [38,39] made small parallelplate capacitors using 'thin films' that were directly milled from bulk single crystals using a Focused Ion Beam Microscope (FIB). Almost free-standing single crystal lamellae of BaTiO 3 down to ~75 nm were machined, and their functional properties tested, with the remarkable observation that bulk-like permittivities persisted, even in the thinnest films.…”
Section: Feature Articlementioning
confidence: 99%
“…Despite this level of consensus, recent experimental work hints that parasitic dielectric dead-layers might not be intrinsic at all, or if they are, their presence is much less obvious than originally thought: Initially in response to concerns that permittivity suppression might result from microstructural imperfections [34][35][36] or from substrate clamping [37], Saad et al [38,39] made small parallelplate capacitors using 'thin films' that were directly milled from bulk single crystals using a Focused Ion Beam Microscope (FIB). Almost free-standing single crystal lamellae of BaTiO 3 down to ~75 nm were machined, and their functional properties tested, with the remarkable observation that bulk-like permittivities persisted, even in the thinnest films.…”
Section: Feature Articlementioning
confidence: 99%
“…It is clearly demonstrated that elastic domains can be sufficiently mobile in constrained ferroelectric films, and the relatively small extrinsic piezoeffect in the epitaxial films can be explained by elastic interactions between the clamped film and substrate. The extrinsic piezoeffect can be increased significantly by reducing the elastic clamping, as is supported by the experimental results on polydomain ferroelectric thin film "islands" with a lateral size comparable to their thickness [13,23].…”
Section: Introductionmentioning
confidence: 56%
“…Transmission electron microscopy (TEM) [25] and piezoelectric force microscopy (PFM) [13,23] studies of tetragonal PZT 20/80 films thicker than 300 nm show that they have a cellular architecture that completely relaxes the internal stresses. An optical microscopy study of epitaxial tetragonal BaTiO 3 thick films also illustrates similar morphology of a three-domain structure [14].…”
Section: Thermodynamics Of Three-domain Film In the Absence Of Electrmentioning
confidence: 99%
See 2 more Smart Citations